Pertanggungjawaban PPAT dalam Proses Jual Beli Tanah yang Berakibat Tindak Pidana Penggelapan (Studi Putusan Nomor 69/Pid/2020/PT. SMR) - Bertha Milionita S; hasim purba; mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
PPAT as a public official has the authority to create land sale and purchase deeds and is obligated to apply the prudential principle. This study of Decision Number 69/Pid/2020/PT. Smr analyzes PPAT's accountability in land sale and purchase processes resulting in criminal embezzlement. There is no concrete regulation regarding PPAT's prudential principle, creating legal ambiguity. Embezzlement by PPAT should be subject to Article 374 of the Criminal Code (embezzlement in office), but the judge erroneously applied Article 372 of the Criminal Code. Clearer regulations are needed regarding prudential indicators and embezzlement acts by PPAT, as well as more comprehensive judicial considerations in deciding similar cases to establish legal certainty.